IMPORTANCE OF PUBLIC WAREHOUSE SYSTEM FOR FINANCING AGRIBUSINESS SECTOR - Zakić, Vladimir; Kovačević, Vlado; Ivkov, Ivana; Mirović, Vera (Economics of Agriculture, 2014)
The aim of this study was to determine the economic viability of the use of warehouse receipts for the storage of wheat and corn, based on the analysis of trends in product prices, storage costs in public warehouses and interest rate of loans against warehouse receipts. Agricultural producers are urged to sell grain at the harvest time when the price of agricultural products is usually lowest, mostly because of their needs for financial sources. Instead of selling products, farmers can store them in the public warehouses and use short time financing by lending against warehouse receipt with usually lowest interest rate. In following months, farmers can sell products at higher price and repay short-term loan. This study showed that strategy of using public warehouses and postponing the sale of grains after harvest is profitable strategy for agricultural producers.